Building performance optimization strategies and practices - a impact and achievement on sustainable built environment / Alia Abdullah Saleh, Hasnan Hashim , Noorazlina Kamarulzaman - Abdullah Saleh, Alia; Hashim, Hasnan; Kamarulzaman, Noorazlina (2012)
Building performance optimization is one of the trivial of the building characterization according to sustainable built environment approach. The introduction of Optimize Building Performance and System Control Strategies helps to optimize the usage for building in particular to Productivity, Functional or Operational - Product or Systems Integration, Meet Performance Objectives. Aesthetics Preservation, Secure or Safe, Sustainable - Optimize Site Potential, Protect and Conserve Water, Use Environmentally Preferable Products, Enhance Indoor Environmental Quality and Optimize Operational and Maintenance Practices. The building industry has been judged to consume large quantities of material resources and energy. So as to promote sustainability in this sector, definite intend and programs need to be cultivated to nurture awareness among team member, including developers, owners, designers, engineers, contractor, occupant and authorities. The anticipated finding of this research is to substantiate the importance of building performance optimization including whole building design process, cost effective, functional or operational, productive, Building Information Modeling (BIM), products and systems, energy efficiency programs, building commissioning, operational and maintenance practices, Facility Performance Evaluation, Codes and Compliances Standard and associated strategies including Building Monitoring, High-Efficiency Equipment, Life Cycle Assessment, Rightsizing Equipment, Staff Training, Systems Tune-up and Total Building Commissioning